2013 Curriculum: Implementation of Islamic Religious Education Learning in Schools for Children with Special Needs - Yayah Nurmaliyah; Syamsul Aripin; Nana Meily Nurdiansyah (Sekolah Tinggi Agama Islam Taruna Surabaya, 2023)
The 2013 curriculum is the latest guideline for implementing education in Indonesia. Its application applies to public schools and special schools. This study aims to determine how to implement the 2013 curriculum in learning Islamic religious education for children with special needs (ABK) at SLB Negeri 01 Jakarta. This study uses qualitative research with a descriptive approach to data collection techniques with interviews, observation, and documentation. Data were collected based on field notes, comments, and documentation. The results of the study concluded that the implementation of the 2013 Curriculum for Children with Special Needs (ABK) at SLB Negeri 01 Jakarta uses the same PAI curriculum as the curriculum in traditional schools, and the scope of Islamic Religious Education materials taught is no different from other schools including; al-Qur'an hadith, faith, morals, fiqh and the history of Islamic culture. The learning methods for Islamic Religious Education in special schools are lectures, practices, questions and answers, demonstrations, and exercises. The learning media used include audio-visual media, tape recorders, films, radio, television, digital al-Qur'an, and braille Qur'an are also puzzles. Learning Evaluation consists of three domains cognitive, affective, and psychomotor.